2020
DOI: 10.1016/j.neuroscience.2019.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Induced by (S)-3,5-Dihydroxyphenylglycine Postconditioning is Mediated by the PI3K/Akt/GSK3β Signalling Pathway in an In Vitro Model of Cerebral Ischemia

Abstract: Ischemic postconditioning (PostC) is an endogenous neuroprotective strategy for cerebral ischemia induced by low activation of glutamate receptors. We have previously shown that the application of the mGluR1/5 agonist (S)-3,5-dihydroxyphenylglycine (DHPG) 5 min after 30 min of oxygen and glucose deprivation (OGD) reduces CA1 damage in organotypic hippocampal slices by activating the PI3K-Akt signalling pathway. In order to extend these data, we analysed the production of reactive oxygen species (ROS) and the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Moreover, it has been shown that the mGluR1/5 agonist DHPG can be used as a pre‐ and post‐conditioning stimulus, being able to protect CA1 pyramidal cells in rat hippocampal slices from the deleterious effects of 30 min oxygen and glucose deprivation (OGD); (Blaabjerg, 2003; Gerace, Scartabelli, et al, 2012; Gerace, Scartabelli, Pellegrini‐Giampietro, & Landucci, 2020; Scartabelli, Gerace, Landucci, Moroni, & Pellegrini‐Giampietro, 2008; Werner et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the mGluR1/5 agonist DHPG can be used as a pre‐ and post‐conditioning stimulus, being able to protect CA1 pyramidal cells in rat hippocampal slices from the deleterious effects of 30 min oxygen and glucose deprivation (OGD); (Blaabjerg, 2003; Gerace, Scartabelli, et al, 2012; Gerace, Scartabelli, Pellegrini‐Giampietro, & Landucci, 2020; Scartabelli, Gerace, Landucci, Moroni, & Pellegrini‐Giampietro, 2008; Werner et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We then examined the effects of UCB, pioglitazone and allopurinol on neuronal death and oxidative stress in an in vitro model of ischemic preconditioning in immature slices, in order to mimic what could occur in preterm infants following IH events. Ischemic preconditioning was obtained by exposing the slices to 10 min OGD, as previously reported in Gerace et al (35,45,46). For these experiments, organotypic hippocampal slices were exposed to UCB, UCB plus pioglitazone or UCB plus allopurinol immediately after 10 min OGD preconditioning and maintained for 24 h (Figure 6A).…”
Section: Effects Of Ucb Pioglitazone and Allopurinol On Neuronal Death And Oxidative Stress In An In Vitro Model Of Ischemic Preconditionmentioning
confidence: 95%
“…Cultures were exposed to oxygen and glucose deprivation (OGD) in order to mimic what occur after HI episodes and HIE, as previously reported in detail (35,(44)(45)(46). Briefly, OGD was reproduced by exposing the slices to serum-and glucose-free medium saturated with 95% N 2 and 5% CO 2 for 30 min at 37 • C in an airtight anoxic chamber equipped with an oxygen gas controller (BioSpherix, New York, USA).…”
Section: Ogd Protocol In Rat Organotypic Hippocampal Slicesmentioning
confidence: 99%
See 2 more Smart Citations